Perception of employees on transfer of knowledge from training programs at Ceva Freight Holdings (M) Sdn Bhd / Fatin Filzah Sapri and Ahmad Junaidi Rosly - Sapri, Fatin Filzah; Rosly, Ahmad Junaidi (Faculty of Business and Management, 2014)
The study was undertaken at CEVA Freight Holdings (M) Sdn Bhd on the topic “Perception of Employees on Transfer of Knowledge from Training Programs at CEVA Freight Holdings (M) Sdn Bhd”. The purpose of this study was to determine the most influencing factors which affect the perception of employees on transfer of knowledge from training programs and to recommend some measures in enhancing the perception of employees on transfer of knowledge from training programs with CEVA Freight Holdings (M) Sdn Bhd as a case study. Primary data was collected from a sample of hundred (100) employees. Self-administered questionnaire was used in the collection of data for analysis. The study revealed that there were organizational issues such as lack of employer support on transfer of knowledge from training programs in employees work field. It was also found that employee competencies are the main role to achieve the effectiveness on transfer of knowledge from training programs in CEVA. The study recommended that in order for CEVA Freight Holdings (M) Sdn Bhd to be successful in the transfer of knowledge from training programs, employer should focus on performance of employees and encourage the flow of knowledge in their work field to achieve the performance standard in an organization.